Antimicrobial activity of natural compounds from sponge – derived fungus Aspergillus flocculosus 01NT.1.1.5 - Trinh, Phan Thi Hoai; Thanh Van, Tran Thi; Minh Ly, Bui; Kyu Choi, Byeoung; Jae Shin, Hee; Seok Lee, Jong; Seung Lee, Hyi; Quyet Tien, Phi (Vietnam Journal of Biotechnology, 2020)
The Aspergillus fungi have been an important source of natural products that are useful for exploration in medicine, agriculture and industry. In our continuous investigation to search for new antimicrobial agents from marine-derived fungi, one new phomaligol A2 (1), together with three known compounds, wasabidienone E (2), aspertetranone D (3) and mactanamide (4), were obtained from the EtOAc extract of the culture medium of the marine-derived fungus Aspergillus flocculosus (A. flocculosus) 01NT.1.1.5 isolated from the sponge Stylissa sp. at Nhatrang Bay, Vietnam. Their chemical structures were elucidated by analysis of 1D and 2D NMR and mass spectroscopic data, as well as by comparison of the corresponding data to those previously reported in the literature. Furthermore, the aim of this study was also to evaluate the antimicrobial activity of these compounds against pathogenic microbes including Escherichia coli (E. coli) ATCC 25922, Pseudomonas aeruginosa (P. aeruginosa) ATCC 27853, Staphylococcus aureus (S. aureus) ATCC 25923, Bacillus cereus (B. cereus) ATCC 11778, Streptococcus faecalis (S. faecalis) ATCC 19433, Listeria monocytogenes (L. monocytogenes) ATCC 19111, and Candida albicans (C. albicans) ATCC 10231. Among the compounds, 1-3 were inhibitory on the growth of the yeast C. albicans with minimum inhibitory concentration (MIC) value of 16 μg/mL, which was more potent than amoxicillin and cefotaxime (MIC > 256 μg/mL), antimicrobial drugs as positive references. Moreover, compounds 1-4 were also found to be active against other pathogens including P. aeruginosa and S. faecalis with MIC values of 16 μg/mL and 32 μg/mL, respectively. Compound 4 had no inhibitory activity against L. monocytogenes, whereas compounds 1-3 had ability to against this strain with MICs of 32 to 64 μg/mL. Four of tested compounds exhibited antibacterial activity against B. cereus and E. coli with MIC values of 64-128 μg/mL. This is the first report about these compounds with antimicrobial activity obtained from marine fungus A. flocculosus isolated in Vietnam.